Resettlers and survivors : Bukovina and the politics of belonging in West Germany and Israel, 1945-89 - Fisher, Gaëlle, 1985- (New York : Berghahn, 2020)
"Located on the border of present-day Romania and Ukraine, the historical region of Bukovina was the site of widespread displacement and violence as it passed from Romanian to Soviet hands and back again during World War II. This study focuses on two groups of 'Bukovinians'--ethnic Germans and German-speaking Jews--as they navigated dramatically changed political and social circumstances in and after 1945. Through comparisons of the narratives and self-conceptions of these groups, Resettlers and Survivors gives a nuanced account of how they dealt with the difficult legacies of World War II, while exploring Bukovina's significance for them as both a geographical location and a 'place of memory.' "--
Acknowledgements Introduction Part I: Backgrounds Chapter 1. Being Bukovinian before 1945: German and Jewish Bukovinians in the Habsburg Empire, Romania, and World War II Part II: Establishments Chapter 2. 'Settling in the Motherland': 'Resettlers' from Bukovina in West Germany after World War II; Chapter 3. 'A remarkable branch of the Jewish people': Survivors from Bukovina between Romania and Israel after World War II Part III: Entanglements Chapter 4. 'Lost Home' and 'Area of Expulsion': Compensating for Loss at the Height of the Cold War; Chapter 5. 'Sunken Cultural Landscape': Reimagining Bukovina through the Lens of Literature Conclusion Bibliography; Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 15, 2020).
JSTOR
Keywords: Jews -- Bukovina (Romania and Ukraine) -- History -- 20th century; Jews, Romanian -- Israel -- History -- 20th century; Jews, Ukrainian -- Israel -- History -- 20th century; Germans -- Israel -- History -- 20th century; Ukrainians -- Israel -- History -- 20th century; Romanians -- Israel -- History -- 20th century; Ukrainians -- Ethnic identity; Romanians -- Ethnic identity; Germans -- Ethnic identity; Collective memory -- Bukovina (Romania and Ukraine); Bukovina (Romania and Ukraine) -- Ethnic relations -- History -- 20th century; Bukovina (Romania and Ukraine) -- Emigration and immigration; Juifs -- Bucovine (Roumanie et Ukraine) -- Histoire -- 20e siècle.; Allemands -- Israël -- Histoire -- 20e siècle.; Ukrainiens -- Israël -- Histoire -- 20e siècle.; Roumains -- Israël -- Histoire -- 20e siècle.; Ukrainiens -- Identité ethnique; Roumains -- Identité ethnique; Allemands -- Identité ethnique; Mémoire collective -- Bucovine (Roumanie et Ukraine); Juifs roumains -- Israël -- Histoire -- 20e siècle.; HISTORY / Europe / Eastern; Collective memory; Emigration and immigration; Ethnic relations; Germans; Germans -- Ethnic identity; Jews; Jews, Romanian; Jews, Ukrainian; Romanians; Romanians -- Ethnic identity; Ukrainians; Ukrainians -- Ethnic identity; Europe -- Bukovina; Israel; 1900-1999; History